2015
DOI: 10.1200/jop.2014.002741
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Unplanned Care From Clinician Notes in Electronic Health Records

Abstract: Purpose: Reduction in unplanned episodes of care, such as emergency department visits and unplanned hospitalizations, are important quality outcome measures. However, many events are only documented in free-text clinician notes and are labor intensive to detect by manual medical record review. Methods:We studied 308,096 free-text machine-readable documents linked to individual entries in our electronic health records, representing care for patients with breast, GI, or thoracic cancer, whose treatment was initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…[27,28,29,30] Outside of rheumatology, researchers have developed text data extractors for dementia diagnoses and cancer staging, urinary incontinence-related PROs, identification of out-of-network emergent care encounters, disease phenotyping, and extraction of documentation of advanced directives. [31,32,33,34] This work has shown that important healthcare outcomes are being captured in EHRs as free text and that although challenges exist, NLP and machine learning methods may be increasing feasible options for accurately and efficiently identifying health outcomes.…”
Section: Improving Disease Outcomes In Ramentioning
confidence: 99%
“…[27,28,29,30] Outside of rheumatology, researchers have developed text data extractors for dementia diagnoses and cancer staging, urinary incontinence-related PROs, identification of out-of-network emergent care encounters, disease phenotyping, and extraction of documentation of advanced directives. [31,32,33,34] This work has shown that important healthcare outcomes are being captured in EHRs as free text and that although challenges exist, NLP and machine learning methods may be increasing feasible options for accurately and efficiently identifying health outcomes.…”
Section: Improving Disease Outcomes In Ramentioning
confidence: 99%
“…We customized our approach for identifying cases of urinary incontinence documented in free text using an approach that has been previously applied to develop task-specific extractors. 30 With the aim of improving sensitivity, we enhanced the annotator’s terminology to include additional terms relevant to urinary incontinence (e.g., “wears adult diapers”). In addition, we extended the basic set of rules provided by NegEx to consider additional contextual information such as the following: hypothetical terms, e.g., “at risk for” (urinary incontinence); historical terms, e.g., “past history of” (urinary incontinence); and discussion terms, e.g., “discussed complications such as” (urinary incontinence).…”
Section: Methodsmentioning
confidence: 99%
“…To leverage the scale and richness of EHR for clinical decisions, particularly in emergencies and in the absence of evidence from randomized control trials, timely and accurate synthesis of evidence through automated methods is necessary. Toward that vision, advances have been made with automatic cohort selection via electronic phenotyping [ 13 ], natural language processing [ 66 , 67 ], patient similarity [ 8 ] and automatic confounder control by PS methods [ 17 , 19–22 , 24–27 ]. This study supplements automation efforts by demonstrating that there exist automated alternatives to expert-based PS, including non-PS-based methods, for confounder control.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%